Synthesis and characterization of lithium transition orthosilicates Li2FexMn1-xSiO4 as cathode material - Ritesh Kumar; A.L. Sharma; R.K. Singh; Arvind Kumar; Pramod K. Singh; M.Z.A. Yahya; S.N.F. Yusuf; Markus Diantoro; Manoj K. Singh (Chemical Physics Impact)
Recently, lithium metal orthosilicates Li2FeSiO4 and Li2MnSiO4 are attracted attention as a cathode material for Li-ion batteries. Here, Li2FexMn1-xSiO4 (x = 0.3, 0.5, 0.7) cathode materials are synthesized by using sol-gel method, and physically characterized via X-ray diffraction (XRD), Field emission scanning electron microscopy (FESEM), and Energy dispersive X-ray (EDX). The FESEM images confirm the cubical shape particles in nanometers scale. The EDX mapping indicates the presence of iron, manganese, and silicates in different samples. The Li-ion batteries are assembled with gel polymer electrolyte PVdF-HFP/LiClO4/EC-PC, and Li2FexMn1-xSiO4 (x=0.3, 0.5, 0.7) cathode and graphite anode. The assembled cells are electrochemically characterized by cyclic voltammetry (CV), and galvanostatic charge-discharge (GCD) techniques. It is observed that the oxidation and reduction peaks of the cells shifted as scan rate increases which indicate the charge transfers are diffusion controlled at the interface. The cell Li2Fe0.5Mn0.5SiO4//graphite offers highest discharge capacity∼220 mAh g-1 at 1 mA cm-2.